2018
DOI: 10.1002/lary.27616
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Analgesia for Patients Undergoing Septoplasty and Rhinoplasty: An Evidence‐Based Review

Abstract: Objectives/Hypothesis Opioid misuse and diversion is a pressing topic in today's healthcare environment. The objective of this study was to conduct a review of non‐opioid perioperative analgesic regimens following septoplasty, rhinoplasty, and septorhinoplasty. Study Design Evidence‐based systematic review. Methods PubMed, MEDLINE, Cochrane Library, and Embase databases were reviewed for articles related to perioperative analgesic use in septoplasty, rhinoplasty, and septorhinoplasty. Quality of studies were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 51 publications
2
43
0
2
Order By: Relevance
“…An evidence‐based review on non‐opioid perioperative analgesic regimens following septoplasty, rhinoplasty, and septorhinoplasty found that NSAIDS, gabapentin, α‐agonists, and local anesthetics were as effective as opioid alternatives in terms of perioperative analgesia. In that study, the use of local anesthetic was found to be a safe, rapid‐onset action, and a cost‐effective option in reducing postoperative pain scores and rescue analgesic requirements …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An evidence‐based review on non‐opioid perioperative analgesic regimens following septoplasty, rhinoplasty, and septorhinoplasty found that NSAIDS, gabapentin, α‐agonists, and local anesthetics were as effective as opioid alternatives in terms of perioperative analgesia. In that study, the use of local anesthetic was found to be a safe, rapid‐onset action, and a cost‐effective option in reducing postoperative pain scores and rescue analgesic requirements …”
Section: Discussionmentioning
confidence: 98%
“…Despite considerable improvements in analgesia and surgical techniques, there is no consensus for pain control and avoidance of overprescription after nasal surgery. Numerous pain medications, such as nonsteroidal anti‐inflammatory drugs (NSAIDS), gabapentin with or without intravenous dexamethasone, opioids, and multimodal or balanced analgesic protocols that include non‐opioid analgesic drugs such as paracetamol, and various NSAIDS in combination with low doses of opioids were previously studied for postoperative pain management after nasal surgery . However, systemic use of these agents is associated with potential side effects .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low pain level of the patient will speed up recovery, provide a comfortable process and minimize the cost [12]. It is beneficial for the patient to apply a local anesthetic agent to the surgical area during the surgery, as it causes decreased postoperative pain scores and additional analgesic requirements [13]. In a recent study, the addition of a local anesthetic agent to the nasal packs after septal surgery has been shown to have positive effects in reducing postoperative pain within the first 12 hours [14].Steroids such as methylprednisolone are used due to anti-inflammatory and immunosuppressive effects [15].…”
Section: Discussionmentioning
confidence: 99%
“…Low pain level of the patient will speed up recovery, provide a comfortable process and minimize the cost [11]. It is beneficial for the patient to apply a local anesthetic agent to the surgical area during the surgery, as it causes decreased postoperative pain scores and additional analgesic requirements [12]. In a recent study, the addition of a local anesthetic agent to the nasal packs after septal surgery has been shown to have positive effects in reducing postoperative pain within the first 12 hours [13].…”
Section: Discussionmentioning
confidence: 99%